The activity of some dehydrogenases in tissues of Black Sea mussels under the action of heavy metal chlorides - Семенова, О. O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The effect of copper, lead and cadmium chlorides on the activity of pyruvate dehydrogenase complex and TCA cycle dehydrogenases in tissues of Black Sea mussels has been studied. The concentration of 10 mg/L of cadmium chloride in water does not change the activity of the enzymes. A similar concentration of copper chloride reduces the activity of multienzyme complexes, and lead chloride inhibits all studied dehydrogenase.